Manifestations of poverty and health conditions of residents of the urban fringe a field study in the chaotic neighborhood of Borj Al-Senussi and the tin housing at the foot of the Red Mountain 'Amqran' Boukhnfous, In the city of Laghouat, Algeria - Badawi, Abdelkader; Aoun, Zoubir Ben; Taibi, Nawal (International journal of health sciences, 2024)
Through this study, we aim to identify the manifestations of poverty for the inhabitants of the urban margins, who live in a deteriorating housing and urban condition, and in order to come up with realistic results, we used the descriptive approach, and we used scientific observation and interview to collect information from the field from a sample of heads of households, settled in the chaotic neighborhood of Borj Al-Senussi and the tin housing scattered at the foot of the Red Mountain "Amqran" in the Boukhanfoss area in the city of Laghouat, and after presenting and analyzing the data, we concluded that these neighborhoods and their residents live in a privileged state of poverty, and this is evident through the fragile nature of the tin housing, suffering from difficult social and economic conditions that led them to spatially isolated from urban and social field.